Philosophy of Science with Counseling Practice in Building Guidance and Counseling Science that Keeps Up with the Times - Rober Sandra; Yeni Karneli; Puji Gusri Handayani (Ilmina: Journal of Education and Counseling, 2025)
The evolving demands of the modern era require the field of Guidance and Counseling to go beyond technical practices and embrace a strong philosophical foundation. This study aims to explore the collaboration between philosophy of science and counseling practice as a strategic effort to develop a reflective and adaptive scientific paradigm. Employing a qualitative research design with a literature review method, data were collected from relevant academic sources and analyzed using content analysis techniques. The findings reveal that integrating the philosophy of science enriches counselors' frameworks and addresses the fragmentation within the discipline. This study contributes to the formulation of counselor education models that emphasize critical reflection and contextual value integration. The conclusion highlights the urgency of reconstructing curricula and suggests future empirical research to evaluate the practical implementation of this integration in real world counseling contexts.